Correlation of steam explosion severity with morphological and physicochemical characterization of soybean meal - Zeng, Qinghua; Kong, Feng; Li, Yue; Guo, Xingfeng (Frontiers in Sustainable Food Systems, 2022)
Steam explosion, a novel effective technology for cereal modification, integrates high-temperature autohydrolysis and structural disruption, which can significantly influence the morphological and physicochemical characterization of the feedstocks. The deep knowledge of the structural changes that are brought about by the treatment severity is connected with the technological demands to improve the processing efficiency and to increase the industrial application of the feedstocks by steam explosion. In this study, the changes in morphological and physicochemical properties of soybean meal induced by steam explosion were investigated. The correlation of steam explosion severity with soybean meal's final quality was also analyzed. The results showed that steam explosion effectively increased the fractal dimension from 1.6553 to 1.8871, the glycinin content from 151.38 to 334.94 mg/g, and the 2,2-diphenylpicrylhydrazyl (DPPH) radical scavenging activity from 28.69 to 63.78%. The gray value, color (L* and a* values), and the total phenol and polysaccharide contents of soybean meal were reduced with greater steam explosion severity. Steam explosion severity had a remarkable positive correlation with the fractal dimension and DPPH radical scavenging activity. However, steam explosion severity had no significant correlation with the textural and adsorption properties of the soybean meal. This study focused on the morphological and physicochemical property changes of the soybean meal during a steam explosion process, which could guide the application of steam explosion in food systems.